The development of a porcine 50K SNP panel using genotyping by target sequencing and its application - Zipeng Zhang; Siyuan Xing; Ao Qiu; Ning Zhang; Wenwen Wang; Changsong Qian; Jia’nan Zhang; Chuduan Wang; Qin Zhang; Xiangdong Ding (Journal of Integrative Agriculture, 2025)
Genotyping by target sequencing (GBTS) integrates the advantages of silicon-based technology (high stability and reliability) and genotyping by sequencing (high flexibility and cost-effectiveness). However, GBTS panels are not currently available in pigs. In this study, based on GBTS technology, we first developed a 50K panel, including 52,000 single-nucleotide polymorphisms (SNPs), in pigs, designated GBTS50K. A total of 6,032 individuals of Large White, Landrace, and Duroc pigs from 10 breeding farms were used to assess the newly developed GBTS50K. Our results showed that GBTS50K obtained a high genotyping ability, the SNP and individual call rates of GBTS50K were 0.997–0.998, and the average consistency rate and genotyping correlation coefficient were 0.997 and 0.993, respectively, in replicate samples. We also evaluated the efficiencies of GBTS50K in the application of population genetic structure analysis, selection signature detection, genome-wide association studies (GWAS), genotyped imputation, genetic selection (GS), etc. The results indicate that GBTS50K is plausible and powerful in genetic analysis and molecular breeding. For example, GBTS50K could gain higher accuracies than the current popular GGP-Porcine bead chip in genomic selection on 2 important traits of backfat thickness at 100 kg and days to 100 kg in pigs. Particularly, due to the multiple SNPs (mSNPs), GBTS50K generated 100K qualified SNPs without increasing genotyping cost, and our results showed that the haplotype-based method can further improve the accuracies of genomic selection on growth and reproduction traits by 2 to 6%. Our study showed that GBTS50K could be a powerful tool for underlying genetic architecture and molecular breeding in pigs, and it is also helpful for developing SNP panels for other farm animals.